UPPER CRETACEOUS (MAASTRICHTIAN) LANDVERTEBRATE DIVERSITY IN ALBA DISTRICT (ROMANIA) - Codrea, V.; Barbu, O.; Jipa-Murzea, C. (Bulletin of the Geological Society of Greece, 2010)
In Romania, Maastrichtian (Late Cretaceous) dwarf dinosaur remains were first reported from the Haţeg basin by the Baron Franz Nopcsa, at the end of 19th century. Later, the same expanded his research to others areas of Transylvania, adding new localities with comparable Maastrichtian vertebrate assemblages in Alba and Sălaj Counties. Following Nopcsa, both these regions and topics have not been studied for a long time. In the last decade, new field works succeeded in finding rich and diverse Maastrichtian terrestrial vertebrate fauna in Alba County restricted to a distinct Late Cretaceous sedimentary area (Metaliferi). For these studies, the Şard Formation is of main interest. In this formation, the Maastrichtian is developed in fluvial system environments which are documented by flood plain overbank and channel fill deposits. Besides fishes, amphibians, birds and mammals, the fossils embrace mainly various dinosaurs such as sauropods, hadrosaurs, ornithopods, ankylosaurs, various small-sized theropods, as well as other reptiles as turtles and crocodilians. Often, the remains are fragmentary and dislocated. Besides the Haţeg basin, the Metaliferi area is the second important region documenting the Maastrichtian terrestrial biota in Romania.